Surrender : 40 songs, one story - Bono, 1960-; Bono, 1960- (New York : Alfred A. Knopf, 2022)
Bono writes about his remarkable life for the first time, from his early days growing up in Dublin, to U2$1 (Bs meteoric rise to fame, to his more than twenty years of activism dedicated to the fight against AIDS and extreme poverty.s
Part I. Lights of home ; Out of control ; Iris (Hold me close) ; Cedarwood Road ; Stories for boys ; Song for someone ; I will follow ; 11 o'clock tick tock ; Invisible ; October ; Two hearts beat as one ; Sunday Bloody Sunday ; Bad ; Bullet the blue sky ; Where the streets have no name ; With or without you ; Desire -- Part II. Who's gonna ride your wild horses ; Until the end of the world ; One ; The fly ; Even better than the real thing ; Mysterious ways ; Stuck in a moment ; Wake up dead man ; The showman ; Pride (In the name of love) -- Part III. Beautiful day ; Crumbs from your table ; Miracle drug ; Vertigo ; Ordinary love ; City of blinding lights ; Get out of your own way ; Every breaking wave ; I still haven't found what I'm looking for ; Love is bigger than anything in its way ; Moment of surrender ; Landlady ; Breathe.
Keywords: Bono, -- 1960-; U2 (Musical group); Rock musicians -- Biography; Human rights workers -- Biography; Musicians -- Biography; Autobiographies